Effect of spacings and fertilizers on growth, yield and physical fruit quality of chilli (Capsicum annuum L.) cultivars - PORWAL, J P S PUNDIR, R (Journal of Spices and Aromatic Crops, 1999)
The effect of spacings and fertilizers on growth, yield and fruit quality (physical) of chilli (Capsicum annuwn) cultivars was studied at Bikaner (Rajasthan, India). The cultivar Local Desi recorded significantly higher plant height, dry weight per plant, weight and volume per fruit. However, cultivar NP 46 prodnced maximum number of fruits per plant, fruit yield per plant and fruit yield per hectare. Application of 100 kg N in combination with 25 kg P and 50 kg K per ha recorded highest fruits per plant. Maximum plant height, fresh weight and dry weight per plant, number of fruits and yield of fruits per plant were recorded in the widest spacing (55 cm x 55 cm); closest spacing (25 cm x 25 cm) produced highest fruit yield per hectare. The quality offruits was affected by spacings. Interaction effect of spacings, fertilizers and cultivars was non significant to affect growth, yield and fruit quality attributes.